Calculation model of concrete-filled steel tube arch bridges based on the “arch effect” - Wang, Shaorui; Li, Yingbin; Liu, Zengwu; Cheng, Tianlei (Frontiers in Materials, 2023)
In view of the limitations of the current code based on the equivalent beam-column method with the “rod mode” instead of the “arch mode” for the calculation of concrete-filled steel tube arch bridges, this paper takes the real bearing mechanism of the arch as the starting point and analyzes the different bearing mechanisms of the arch and eccentric pressurized column. The concrete-filled steel tube arch model test was carried out to analyze the deformation state and damage mode, and the geometric non-linear bending moment of the measured arch was compared with the bending moment value calculated by the eccentricity increase coefficient of the “rod mode.” The results showed that the transfer of internal force is from the axial force to the arch axis, causing the vertical reaction force and horizontal thrust. However, the eccentric compression column only produced the vertical force at the bottom and combines with the lateral deformation indirectly generated by the eccentric distance. In addition, the deformation stage of the arch is basically the same as that of the eccentric compression column. The final failure mode of the arch is 4-hinge damage, and the final failure mode of the eccentric compression column is single-hinge damage. The preliminary geometric non-linear bending moment value obtained by the two modes accords well. Therefore, the main factors for the difference in the bearing mechanism between the two modes are different force structures, force transmission routes, and sources of deformation. Due to the difference in the bearing mechanism, the final failure mode is different, and the deformation ability of the arch is weakened by using the “rod mode” instead of the “arch mode.” The geometric non-linear bending moment of the control section calculated by the eccentricity increase coefficient is conservative, but the influence of the geometric non-linearity of other sections is not considered enough.